Hoe cultureel mag cultuurgeschiedenis zijn? Rond het IJkpunt 1650 - Frijhoff, W.; Spies, M. (BMGN - Low Countries Historical Review, 2002)
In their rejoinder, the authors of 1650: Bevochten eendracht discuss the main criticisms brought forward by those taking part in the debate at the final conference on the Vantage-points Programme. Basically, they reject two claims as inappropriate with regard to their book and its intentions. Firstly, there can be no question of a political, let alone a holistic framework for this study which is meant to be an interpretation of Dutch culture in the specific language of cultural history. Secondly, they stand up against the reproach that their book would be purely subservient to present-day political questions about identity, Dutchness, and national consensus. Instead, they show that the key terms which they used to describe and explain the specific quality of Dutch culture at its 17th-century zenith (pluriformity, discussion culture, burgher participation, ecumenism of everyday life, etc.) are used in this cross-section of Dutch society as analytical, descriptive terms, without any teleological view towards future developments. Finally, they explain the sense in which the European context should be understood and where the limits of European comparison lie at the moment with regard to 17th-century culture. This response is part of the discussion forum IJkpunt 1650.